Childhood family wealth and mental health in a national cohort of young adults. (December 2016) - Lê-Scherban, Félice; Brenner, Allison B.; Schoeni, Robert F.
Abstract: Purpose: Mental health is critical to young adult health, as the onset of 75% of psychiatric disorders occurs by age 24 and psychiatric disorders early in life predict later behavioral health problems. Wealth may serve as a buffer against economic stressors. Family wealth may be particularly relevant for young adults by providing them with economic resources as they make educational decisions and move towards financial and social independence. Methods: We used prospectively collected data from 2060 young adults aged 18–27 in 2005–2011 from the Panel Study of Income Dynamics, a national cohort of US families. We examined associations between nonspecific psychological distress (measured with the K-6 scale) and childhood average household wealth during ages 0–18 years (net worth in 2010 dollars). Results: In demographics-adjusted generalized estimating equation models, higher childhood wealth percentile was related to a lower prevalence of serious psychological distress: compared to lowest-quartile wealth, prevalence ratio (PR)=0.52 (0.32–0.85) for 3rd quartile and PR=0.41 (0.24–0.68) for 4th quartile. The associations were attenuated slightly by adjustment for parent education and more so by adjustment for childhood household income percentile. Conclusions: Understanding the lifelong processes through which distinct aspects of socioeconomic status affect mental health can help us identify high-risk populations and take steps to minimize future disparities in mental illness. Highlights: Less is known about wealth effects on health compared to other socioeconomic indicators. Family wealth may help protect young adults' mental health. Greater family wealth was associated with better mental health among young adults.